The Role of Micronutrients on Fertility of Women with Polycystic Ovary Syndrome: A Systematic Review - Seyedeh Maryam Khalili; Marjan Havaei; Elnaz Haji Rafiei; Leila Alizadeh; Fereshte Ghahremani; Seideh Hanieh Alamolhoda (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2024)
Introduction: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder and diet can affect it. Considering the high prevalence of polycystic ovary syndrome in women and its negative consequences on fertility, this review study was conducted with aim to investigate the role of micronutrients on the fertility of women with polycystic ovary syndrome.Methods: In this systematic review study, to find the related articles, international databases (ScienceDirect, Embase, Scopus, PubMed) and Persian language databases (Magiran, SID and IranMedex) were searched with different combinations of keywords related to "polycystic ovary syndrome" and " "micronutrients" and "fertility" without time limit until February 2023 using the Verhagen scale.Results: Out of 1080 reviewed articles, finally 13 articles were included in the study. Five studies investigated the indirect mechanisms of micronutrients on factors affecting fertility; in two studies, no statistically significant difference was observed, and in three studies, beneficial effects on insulin metabolism and lipid parameters, regulation of menstruation, regulation of LH/FSH ratio were reported. Of the eight studies that investigated ovarian function, seven studies found improved ovarian function. Most of the studies showed the positive effects of micronutrients on the fertility of women with polycystic ovary syndrome.Conclusion: Micronutrients seem to be associated with improved fertility in women with polycystic ovary syndrome.